Misunderstandings Concerning the Significance of AMS Background 14C Measurements. Issue 3 (30th May 2018) - Taylor, R E; Southon, John R; Santos, Guaciara M
ABSTRACT: We consider one misconception of those who currently reject the general validity of radiocarbon ( 14 C) age determinations older than, at most, 10, 000 BP. There is an allegation that the presence of 14 C reported by accelerator mass spectrometry (AMS) laboratories in their measurements of 14 C infinite age (>100, 000 years) organics used to define background levels, support their point of view. This article has been written for a general audience, primarily for those who have questions about the validity of these arguments. However, they may not be familiar with the literature relevant to providing a clear response to the claims of these individuals. We conclude that, in our view, of all of the possible explanations for the reports of the presence of 14 C in these background samples, the least probable explanation has been advanced by those rejecting the validity of the 14 C time scale in excess of, at most, 10, 000 BP.